Laboratory Investigation of the Leakage Characteristics of Unburied HDPE Pipes. (2015) - Latchoomun, L.; King, R.T.F. Ah; Busawon, K.; Mawooa, D.; Kaully, R.G.
Abstract: In this research work, the leakage characteristics of the viscoelastic material HDPE is investigated and compared to other materials like uPVC which is elastic and galvanised steel which is rigid in nature. Under no axial loading, the deformation in HDPE pipe wall causes the leak aperture to close up under increasing pressure head. As a consequence, the leakage exponent decreases from around 1 to 0.5 with increase in both longitudinal and circumferential crack lengths whereas for uPVC and steel, the leakage exponent increases under similar conditions. Consequently, the increase in discharge rate for increasing pressure in HDPE gets smaller.